Study on Helicopter Antitorque Device Based on Cross-Flow Fan Technology - Du Siliang; Tang Zhengfei; Xu Pei; Ji Mengjiang (International Journal of Aerospace Engineering)
In order to improve low-altitude flight security of single-rotor helicopter, an experimental model of a helicopter antitorque device is developed for wind tunnel test. The model is based on the flow control technology of the cross-flow fan (CFF). Wind tunnel tests show that the model can produce side force. It is concluded that the influence of the CFF rotating speed, the rotor collective pitch, and the forward flight speed on the side force of the model is great. At the same time, the numerical simulation calculation method of the model has been established. Good agreement between experimental and numerical side force and power shows that results of numerical solution are reliable. Therefore, the results in actual helicopter obtained from Computational Fluid Dynamics (CFD) solution are acceptable. This proves that this antitorque device can be used for a helicopter.